EMOTIONAL INTELLIGENCE AND ATTITUDE TO WORK OF NON-ACADEMIC STAFF OF TERTIARY INSTITUTIONS IN KWARA STATE, NIGERIA - Saadu, Usman Tunde (PEOPLE: International Journal of Social Sciences, 2016)
Emotional Intelligence has become popular in the field of work and this makes it more imperative for a staff be it academic or non-academic to have the knowledge and perhaps have the skills of emotional intelligence before he or she can discharge his or her duty effectively. This singular reason inspired the researcher to investigate how level of emotional intelligence can influence attitude of non-academic staff of tertiary institutions in Kwara State to work. Descriptive survey was adopted for this study. All the Non-academic staff of the tertiary institutions in Kwara State constituted population for the study. Stratified was used to select three tertiary institutions in the state and in each of the institution 50 non-academic staff were randomly selected and the total number of 150 non-academic staff were selected as respondents in this study. Two instruments were used to obtain data from the respondents; the first was questionnaire titled emotional intelligence scale and the second instrument was attitude to work scale. These instruments were adapted from Rohana, Kamaruzaman and Zanarial (2009). The instruments were tested for the reliability and the reliability score of 0.88 and 0.75 were obtained for the two instruments respectively. Chi-square statistical analysis was used to test two hypotheses postulated for the study at 0.05 level of significance. The findings of the study revealed that level of emotional intelligence significantly influence the attitude to work of non-academic staff of tertiary institutions in Kwara State i.e. staff with high level of emotional intelligence have positive attitude to work. Also, the study revealed that working experience significantly influence level of emotional intelligence of non-academic staff of tertiary institutions in Kwara State. Based on these findings, the researcher therefore recommended that seminar and workshops should be constantly organized for non-academic staff of tertiary institutions to increase their level of emotional intelligence which will in turn develop their attitude to work and improve the productivity.